The Therapeutic Potential of Borassus flabellifer in Oral Mucosal Regeneration and Repair: A Review - Sheryn Ramaniasari; Cindy Hendrawan; Dian Samuel Hasudungan; Nurul Hidayati (Health & Medical Sciences, 2026)
The oral mucosa is a vital component of the human body, forming the moist lining of the oral cavity and acting as the first barrier against physical, chemical, and microbial insults. Oral mucosal injuries are among the most common conditions in dental practice and may result from mechanical trauma, infections, systemic diseases, or iatrogenic factors. In physically active individuals and athletes, the risk of orofacial injury is significantly higher due to repeated exposure to impact and mechanical stress. Borassus flabellifer, a tropical plant widely used in traditional medicine, has gained attention due to its rich phytochemical content, including flavonoids, polyphenols, and saponins. To evaluate the regenerative potential of Borassus flabellifer as a therapeutic agent for oral mucosal wound healing based on available scientific evidence. A structured literature search was conducted across PubMed, ScienceDirect, and Google Scholar using Boolean search strategies based on the PICO framework. Studies published between 2016 and 2026 were screened according to predefined inclusion criteria. Results: A total of 5 eligible studies were identified and included in this review. The findings consistently demonstrated that Borassus flabellifer exhibits anti-inflammatory and antioxidant properties, which are key mechanisms in promoting wound healing. These studies reported enhanced tissue regeneration, reduced inflammation, and improved healing outcomes associated with its phytochemical constituents. Borassus flabellifer shows promising potential as a natural therapeutic agent for oral mucosal wound healing. Its bioactive compounds support its development as a topical treatment; however, further clinical studies are needed to confirm its efficacy and safety